The Effect of Animated Video Learning Media on Students' Understanding and Independence in the Subject Science Lesson - Erma Agustiningsih; Victor Maruli Old L. Tobing; Hetty Purnamasari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to examine the effect of animated video learning media on the conceptual understanding and learning independence of fourth-grade students in Natural and Social Sciences at Kraton 2 Elementary School in Bangkalan. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group. The research sample consisted of one experimental group that learned using animated videos and one control group that received conventional instruction without animated video media. The instruments used in this study were a conceptual understanding test and a learning independence questionnaire. The data were analyzed using descriptive statistics, an independent samples t-test, effect size analysis, and MANOVA. The findings showed that the experimental group’s conceptual understanding scores increased from 39.12 to 72.00, while the control group’s scores increased from 28.56 to 44.64. In terms of learning independence, the experimental group’s scores increased from 28.12 to 57.84, whereas the control group’s scores increased from 28.36 to 31.12. The independent samples t-test showed statistically significant differences in both variables (p < 0.001). These findings were further supported by large effect sizes, with Cohen’s d = 2.014 for conceptual understanding and Cohen’s d = 3.218 for learning independence. The MANOVA results based on Pillai’s Trace indicated that class had a significant simultaneous effect on students’ conceptual understanding and learning independence (p < 0.001). These findings suggest that animated video learning media can serve as an effective supplementary medium in Natural and Social Sciences learning, although the interpretation of the results should be limited to the context of this study.